The Selection of Forest Plants As Feed Resources and Nesting Site of Dwarf Cuscus (Strigocuscus celebensis) and Nutrient Analysis in Wawonii Island, South-East Sulawesi - Farida, W. Rosa; Dahrudin, H. (JURNAL BIOLOGI INDONESIA, 2008)
ABSTRAKPemilihan Tumbuhan Hutan Sebagai Sumber Pakan dan Tempat Bersarang Kuskus kerdil(Strigocuscus celebensis) dan Analisa Nutrien di Pulau Wawoni, Sulawesi Tenggara. Astudy on feed plants selection and nesting site of dwarf cuscus (Strigocuscus celebensis) wasconducted in Wawonii Island, South-East Sulawesi. The study was done in the lowland forestwith the altitude of 1 - 200 m a.s.l. The results showed 45 species of plants consisting of 23families was selected by dwarf cuscus as their feed resources and 11 species of plants as theirnesting site. Parts of the feed plants being consumed were fruit, young leaves, flower, andtopmost of trunk.Keywords: Forest plant, feed resources, nesting site, Strigocuscus celebensis Wawonii Island